A Ferroelectric Ceramic/Polymer Composite‐Based Capacitive Electrode Array for In Vivo Recordings. Issue 16 (11th May 2017) - Chen, Changyong; Xue, Miaomiao; Wen, Yige; Yao, Guang; Cui, Yan; Liao, Feiyi; Yan, Zhuocheng; Huang, Long; Khan, Saeed Ahmed; Gao, Min; Pan, Taisong; Zhang, Hulin; et al.
Abstract : A new implantable capacitive electrode array for electrocorticography signal recording is developed with ferroelectric ceramic/polymer composite. This ultrathin and electrically safe capacitive electrode array is capable of attaching to the biological tissue conformably. The barium titanate/polyimide (BaTiO3 /PI) nanocomposite with high dielectric constant is successfully synthesized and employed as the ultrathin dielectric layer of the capacitive BaTiO3 /PI electrode array. The performance of the capacitive BaTiO3 /PI electrode array is evaluated by electrical characterization and 3D finite‐element modeling. In vivo, neural experiments on the visual cortex of rats show the reliability of the capacitive BaTiO3 /PI electrode array. This work shows the potentials of capacitive BaTiO3 /PI electrode array in the field of brain/computer interfaces. Abstract : A new implantable capacitive electrode array for electrocorticography signal recording is developed with barium titanate/polyimide (BaTiO3 /PI) nanocomposite. This ultrathin and electrically safe capacitive BaTiO3 /PI electrode array is capable of attaching to the biological tissue conformably. In vivo neural experiments indicate its feasibility. This work shows the potentials of capacitive BaTiO3 /PI electrode arrays in the field of brain/computer interfaces.